Analysis of Fingerprint Patterns and Axial Triradius Digital Angles in Mentawai Children - Aulia, Afifah Mabrukah; Yuniarti, Elsa; Rosalina, Linda; Amran, Rika (Jurnal Biologi Tropis, 2025)
Dermatoglyphic characteristics, including fingerprint patterns and the axial triradius digital (ATD) angle, are widely used as biological markers to assess genetic variation and developmental stability within populations. This study aimed to analyze the distribution of fingerprint patterns and the variation of ATD angles among Mentawai children in West Sumatra. A descriptive cross-sectional design was employed involving 10 Mentawai individuals aged 6–18 years. Fingerprint patterns were collected using the ink-and-paper method, and ATD angles were measured manually with a protractor. The results showed that the most common fingerprint patterns were plain whorl and ulnar loop, each representing 40% of observations. The majority of participants exhibited an ATD angle greater than 45° on both the left (70%) and right (60%) hands. These findings reveal distinctive dermatoglyphic characteristics in Mentawai children, indicating potential genetic influences and intrauterine environmental factors. Overall, this study enhances the scientific understanding of biological diversity within the Mentawai population.